Complex DNA knots detected with a nanopore sensor - Rajesh Kumar Sharma (Nature Portfolio, 2019)
Nanopore microscopy is capable of detecting knots in DNA polymers, a common structural feature. Here the authors show nanopore sensors can map the equilibrium structure of these knots between tight and loose states.